GAMBARAN FAKTOR RESIKO PADA PENDERITA TUBERKULOSIS DI PUSKESMAS DI KABUPATEN BANYUMAS - Fatchurohmah, Wiwiek; Sari, Octavia Permata (Jurusan Kedokteran FK Unsoed, 2014)
Tuberculosis (TB) is a major public health problem. It is estimatedÂ that the total number of patient of TB in Indonesia about 10% of TB worldâs patients. The department of Â health and social Banyumas shows that there were 3.9 casesÂ every 10.000 people.Â In all public health centers in Banyumas district from the year 2004-2008 was still found cases TB lung BTA (+) as source of infection. This research was conducted to determine characteristic of risk factorsÂ of tuberculosis in Banyumas. The research is a descriptive study. Location or will be done in 15 Health Centers in Banyumas District Central Java. The population is patients with tuberculosis BTA (+) that noted in medical records Public Health Center. Number of sample that taken was 15 people who suffer from tuberculosis BTA (+) using purposive sampling techniques. Data taken with an interview usingÂ structured questionnare. Result shows that the majority of respondents live in eligible healthy houseÂ including on density, type of floor and walls. Ventilations are eligible butÂ turn out to be still rarely open that enable increasing humidity, and lower lighting. Risk factors that dominant in respondents are factors smoking and history of contact with the sufferers TB .